Kesantunan Berbahasa dalam Pidato Anies Baswedan pada Acara Kumpul Akbar di Jakarta International Stadium (JIS) - Reyhana; Khalsiah; Masithah Mahsa (Global Action and Education for Society, 2026)
This study aims to describe the linguistic politeness in Anies Baswedan's speech at the Grand Gathering event held at the Jakarta International Stadium (JIS). The research method used is qualitative. The data in this study consist of utterances, with the data source being a video of the speech from Anies Baswedan’s official YouTube channel, with a duration of 36 minutes and 40 seconds. The data collection techniques employed include documentation, observation, and note-taking. The data analysis techniques involve data reduction, data presentation, and drawing conclusions. The results of the study show that Anies Baswedan applies various politeness maxims, such as the tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim.